The Effect of Cold Compresses on Pain in Patients with Lower Leg Varicose Veins (VVTB) Post Evovenous Laser Ablation (EVLA) in the IPJVT Cathlab Action Room, Dr. Saiful Anwar Hospital, East Java Province - Zaerina Efrida; Reny Tri Febriani; Sismala Harningtyas (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: Varicose veins are a manifestation of venous insufficiency syndrome where in this syndrome the blood flow in the veins experiences a retrograde flow direction or backflow towards the legs which then experiences congestion. Minimally invasive surgical therapy such as Endovenous Laser Ablation (EVLA) causes pain, so therapy is needed to reduce pain, one of which is with cold compresses Objectives: The purpose of this study was to identify the effect of cold compresses on pain Methods: The design of this study was observational analytic with a cross-sectional approach, using total sampling technique with a sample of 36 respondents. This research instrument used an observation sheet with a Numeric Rating Scale (NRS). Data analysis with the Wilcoxon test with SPSS IBM Version 23Results:The results showed that most respondents (pre-test) were 23 (63.9%), while most (post-test) experienced mild pain 32 respondents (88.9%). The results of the Wilcoxon statistical test obtained a p value = 0.000, which can be concluded that there is an average difference between pre-test and post-test painConclusions: The application of cold compresses can help post-operative patients to reduce the intensity of pain, by giving cold compresses, patients who experience pain feel a cold sensation given using a cold pack on the area of the former operation or around the area of the former operation can smooth blood circulation, reduce post-operative edema that has been performed so that patients feel reduced pain after being given the cold compress